2020
DOI: 10.1101/2020.08.13.246413
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structure of the activated Roq1 resistosome directly recognizing the pathogen effector XopQ

Abstract: Plants and animals detect pathogen infection via intracellular nucleotide-binding leucine-rich repeat receptors (NLRs) that directly or indirectly recognize pathogen effectors and activate an immune response. How effector sensing triggers NLR activation remains poorly understood. Here we describe the 3.8 Å resolution cryo-electron microscopy structure of the activated Roq1, an NLR native to Nicotiana benthamiana with a Toll-like interleukin-1 receptor (TIR) domain, bound to the Xanthomonas effector XopQ. Roq1 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
186
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(192 citation statements)
references
References 68 publications
5
186
0
1
Order By: Relevance
“…2017 ; Dong et al. 2018 ; Martin et al. 2020 ); the similar TIR domains between DM10 and RLM1 members make it particularly likely that they oligomerize, which is often an important step in NLR activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2017 ; Dong et al. 2018 ; Martin et al. 2020 ); the similar TIR domains between DM10 and RLM1 members make it particularly likely that they oligomerize, which is often an important step in NLR activation.…”
Section: Discussionmentioning
confidence: 99%
“…2015 ). In addition, many TIR-NLRs carry a post-LRR (PL) domain, which is involved in pathogen effector recognition ( Van Ghelder and Esmenjaud 2016 ; Martin et al. 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Arabidopsis thaliana (Arabidopsis) the RNL subclass consists of two gene families, ACTIVATED DISEASE RESISTANCE 1 (ADR1) and N REQUIREMENT GENE 1 (NRG1), both being required for immune signalling and cell death induction of many other NLRs, particularly TNLs [4][5][6][7][8][9] . CNLs, TNLs and most likely RNLs induce immune signalling and cell death by oligomerization [10][11][12][13] . CNL activation is speculated to result in the formation of a pore-like or membrane disrupting structure of the CC domain (a so-called resistosome) at the plasma membrane (PM) 10,[14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…Activation and signaling by animal NLRs involves oligomerization and interactor recruitment by oligomeric N-terminal assemblies (Bentham et al, 2017). Recent structural elucidation of a full length plant CNL (HOPZ-ACTIVATED RESISTANCE1 (ZAR1); Wang et al, 2019a; Wang et al, 2019b) and TNL (Recognition of XopQ1 (Roq1); Martin et al, 2020b) revealed assembly of pentameric and tetrameric resistosomes by the activated immune receptors, respectively. Resistosome formation is driven by indirect (ZAR1) or direct (Roq1) pathogen effector recognition, nucleotide exchange (ADP/ATP) within the nucleotide-binding domain and profound conformational changes.…”
Section: Introductionmentioning
confidence: 99%
“…In the resistosome formed by activated Roq1, two dimers of TIR domain dimers exhibit a two-fold symmetry. This conformation leads to opening of the NADase active site of the TIR domain and breakdown of NAD + (Horsefield et al, 2019; Wan et al, 2019; Duxbury et al, 2020; Martin et al, 2020b). In the latter case, it is assumed that one of the breakdown products of the TIR domain enzymatic activity, whose molecular identity remains to be determined, functions as a signaling molecule.…”
Section: Introductionmentioning
confidence: 99%